MCT1 expression is independently related to shorter cancer-specific survival in clear cell renal cell carcinoma. (20th October 2021) - de Carvalho, Paulo Afonso; Bonatelli, Murilo; Cordeiro, Maurício Dener; Coelho, Rafael Ferreira; Reis, Sabrina; Srougi, Miguel; Nahas, Willian Carlos; Pinheiro, Celine; Leite, Katia Ramos Moreira
Abstract: Clear cell renal cell carcinoma (ccRCC) has been considered a metabolic disease, with loss of von Hippel-Lindau (VHL) gene and consequent overexpression of hypoxia-inducible factor 1 alpha (HIF-1α), which is central for tumor development and progression. Among other effects, HIF-1α is involved in the metabolic reprogramming of cancer cells towards the Warburg effect involved in tumor cell proliferation, migration and survival. In this context, several proteins are expressed by cancer cells, including glucose and lactate transporters as well as different pH regulators. Among them, monocarboxylate transporters (MCTs) can be highlighted. Our aim is to comprehensively analyze the immunoexpression of MCT1, MCT2, MCT4, CD147, CD44, HIF-1α, GLUT1 and CAIX in ccRCC surgical specimens correlating with classical prognostic factors and survival of patients with long follow-up. Surgical specimens from 207 patients with ccRCC who underwent radical or partial nephrectomy were used to build a tissue microarray. Immunostaining was categorized into absent/weak or moderate/strong and related to all classic ccRCC prognostic parameters. Kaplan–Meier curves were generated to assess overall and cancer-specific survival, and multivariate analysis was performed to identify independent prognostic factors of survival. Multivariate analysis showed that MCT1 together with tumor size and TNM staging, were independently related to cancer-specific survival. MCT1, CD147, CD44 and GLUT1 expression were significantly associated with poor prognostic factors. We show that MCT1 is an independent prognostic factor for cancer-specific survival in ccRCC justifying the use of new target therapies already being tested in clinical trials. Abstract : The immunoexpression of proteins related to the Warburg effect have been comprehensively studied in ccRCC. The main finding is that MCT1 expression is independently related to shorter cancer-specific survival, justifying the use of MCT1 inhibitors to treat solid tumors.